2007
DOI: 10.1186/1479-5868-4-27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of portion size on chronic energy intake

Abstract: Background: This study experimentally examined the effects of repeated exposure to different meal portion sizes on energy intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 17 publications
0
83
0
3
Order By: Relevance
“…They also present bigger -and increasing -portion sizes, which can contribute to an excessive consumption of energy (30,31) . Our data also showed that drinking soft drinks out of home was negatively associated with overweight among women.…”
Section: Discussionmentioning
confidence: 99%
“…They also present bigger -and increasing -portion sizes, which can contribute to an excessive consumption of energy (30,31) . Our data also showed that drinking soft drinks out of home was negatively associated with overweight among women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that consumers consistently underestimate portion size (39) and consume oversized portions when they are presented (40)(41)(42). Consequently, an individual may ingest significant quantities of trans fats when consuming a single portion of a product labeled 0 g trans fat.…”
Section: The Nutrition Facts Panelmentioning
confidence: 99%
“…O importante é que o indivíduo se alimente a cada três horas. Para facilitar o consumo dos alimentos em quantidades adequadas, recomenda-se que o prato do cliente que está submetido à dieta individual seja porcionado à francesa, pela cozinheira ou por outra pessoa da casa, uma vez que o tamanho das porções constitui um fator importante no controle do peso 17 . Além de estimar o valor energético da dieta e sua distribuição em macronutrientes, é recomendável considerar, no planejamento da dieta individual, os princípios da nutrição funcional, que visa recuperar o processo digestivo, promover a detoxificação hepática e o equilí-brio orgânico, e recuperar o estado nutricional do indivíduo, restabelecendo suas reservas orgâ-nicas 18,19 .…”
Section: Dieta Individualizadaunclassified